Anxiety as a Narrative Force: A Freudian Psychoanalytic Analysis of Ian Lightfoot in Onward (2020) - Mundi Rahayu; Zannuba Arrifah (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
Animated films increasingly address psychological struggles, making them important texts for understanding emotional development in popular culture. This study examines the representation of anxiety in the animated film Onward (2020) through the character of Ian Lightfoot and its role in shaping his psychological development. The study aims to analyze the types of anxiety experienced by Ian and how this anxiety is portrayed through the film's visuals and dialogue. Using a descriptive qualitative method and a film studies approach, the research applies Sigmund Freud’s psychoanalytic theory of anxiety—realistic, neurotic, and moral anxiety—as an analytical framework. Freud’s typology of anxiety functions as the primary analytical framework for categorizing Ian’s psychological responses. The data for this study consists of scenes showing Ian's anxiety in certain situations. The analysis results show that realistic anxiety arises because Ian faces real threats, such as learning to drive on the highway, neurotic anxiety is seen in Ian's anxiety when he interacts with his friends, and moral anxiety arises because Ian feels guilty for failing to fulfil his moral responsibilities to his family. Through the representation of these anxieties, the film Onward depicts the process of Ian's character development from a person who lacks confidence to someone who is more emotionally mature.